Who learns more from Afar? Spatial empirical evidence on manufacturing and services - Nina Vujanović (The Vienna Institute for International Economic Studies (wiiw), 2023)
This paper investigates spatial dependence of FDI knowledge spillovers in manufacturing and services using spatial panel techniques applied to the 2006-2014 Bureau Van Dijk's Amadeus firm-level dataset for Croatia and Slovenia. The paper finds diverse results across the two sectors. The distance between regions does not hinder the absorption of foreign knowledge in manufacturing despite the strong marketstealing effects operating within regions as well as spatially. On the other hand, FDI knowledge spillovers decrease service productivity within regions, because of market-stealing effects operating strongly across a smaller geographical scale. However, its impact is lost as knowledge spillovers from more distant neighbours are accounted for, because the poaching of local labour is impeded by distance due to rising costs of labour mobility. The research indicates that for knowledge absorption, geographic distance plays differing roles in manufacturing and services, due to the different nature of the production process.
Keywords: F23; L6; L8; L2; O3; O4; 330; knowledge spillovers; FDI; spatial econometrics; manufacturing; services